PENGARUH RASIO KEUANGAN DAN KONSERVATISME AKUNTANSI, SERTA KONEKSI POLITIK TERHADAP KUALITAS LABA - Ayem, Sri; Lestari, Puji (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to analyze the effect of financial ratios (profitability and liquidity), accounting conservatism, and political connections on the earnings quality of manufacturing companies on the Indonesia Stock Exchange (2019-2023). With a quantitative approach and a sample of 230 observations, the results of multiple linear regression analysis show that: (1) profitability has a negative effect on earnings quality, indicating aggressive accounting practices in companies with high profits; (2) accounting conservatism has a positive effect, strengthening earnings reliability; (3) liquidity and political connections have no effect on earnings quality. The results showed that simultaneously, the four variables affect earnings quality. Theoretical Contribution: This study expands the application of agency theory by integrating internal (financial ratios, conservatism) and external (political connections) factors, and enriches the literature on the determinants of earnings quality. Practical Contribution: These findings serve as a reference for investors in assessing the risk of earnings manipulation, for management in optimizing conservative accounting policies, and for regulators in preparing financial statement supervision standards, especially in companies with political connections.